A Comparative Analysis of KPPU Sanctions on Tender Collusion in Public Procurement in Indonesia - Eduardo, Herroe; Anzani, Ega; Natalia, Titie Syahnaz (Universitas Sang Bumi Ruwa Jurai, 2025)
Collusion in public procurement tenders in Indonesia, particularly in the context of Hajj-related services, has been a persistent issue despite sanctions imposed by the Indonesian Competition Commission (KPPU). This study analyses KPPU’s approach to sanctions and compares it with international best practices to assess the effectiveness of these measures in preventing anti-competitive practices. Case studies of procurement for Hajj souvenirs, equipment, food, and transportation from 2007 to 2018 indicate that KPPU fines have not provided a sufficient deterrent to prevent repeat collusion. Factors such as weak law enforcement, close business relationships between companies, and ineffective oversight contribute to the recurrence of tender collusion. Through a comparative approach, this study provides recommendations for strengthening regulations, enforcing more stringent sanctions, and enhancing oversight to promote fair competition in public procurement in Indonesia.